A Proposed Rehabilitation Approach to Rehabilitate the Working Muscles on the Knee Joint after the Operation to Remove the Bony Spurs Below the Patella Bone for Some Athletes - Shallal Mohammed, Wissam; Saleh MalAllah, Qusay (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in setting up a rehabilitation program that includes a set of exercises whose purpose is to rehabilitate the knee joint after the operation of removing the bony protrusions under the patella bone through strengthening the muscles working on it and comparing this program with the traditional program applied in hospitals. As for the research objectives, they are to prepare a proposed rehabilitation approach to rehabilitate the working muscles on the thigh joint after the process of removing the bony protrusions under the patella bone, as well as to know the effect of the proposed rehabilitative approach to rehabilitate the working muscles on the thigh joint after the process of removing the bony protrusions below the patella bone and the assumptions that the researchers assumed are for the proposed rehabilitative approach An effect on the rehabilitation of the working muscles on the knee joint after the operation to remove the bony protrusions below the patella bone, as well as the proposed rehabilitative approach that develops the strength of the muscles working on the knee joint faster than the traditional method applied in the hospital. In Chapter Three, the researchers used the experimental approach to suit the nature of the study. As for the research sample, it was from the players who underwent the removal of bony protrusions under the patella bone for various reasons, and their number was 6 players. The two researchers used a set of tools and devices for the purpose of the research procedures, as well as homogeneity and parity for the two groups. The exploratory experiment and then the main and the rehabilitative program and the tests used in the research... As for the fourth chapter, the results were presented and discussed, where the researchers concluded by discussing the results that the proposed rehabilitative approach developed the strength of the muscle groups of the thigh after removing the bony protrusions below the patellar bone faster than the approach applicable in the hospital. In light of the conclusions, the researchers recommended the necessity of using static and moving exercises in the rehabilitative curriculum, as static increases the strength of the muscle and moving increases the magnitude of the muscle, and it is followed by athletes after removing the bony protrusions below the patella bone and also for workers in the field of rehabilitation, the need to pay attention to rehabilitative exercises in their rehabilitation programs for the injured to see the effect of the exercises used on the injured and the extent of their development.